EFEKTIVITAS PENGGUNAAN APLIKASI GOOGLE CLASSROOM PADA PEMBELAJARAN BIOLOGI TERHADAP HASIL BELAJAR SISWA KELAS XI IPA SMA NEGERI 1 TALAGA RAYA - Siti Rahmawati; Wa Ode Asniwia; Ismail (Jurnal Biogenerasi, 2022)
This study aims to determine the effectiveness of using the google classroom application in improving the learning outcomes of class XI science students at SMA Negeri 1 Talaga Raya. This research is a pre-experimental research using one group pretest-posttest design. The population in this study were students of class XI IPA SMA Negeri 1 Talaga Raya. The sample in this study was class XI IPA 2 which amounted to 30 students. The technique of collecting data is through giving multiple choice tests before (pretest) and after (posttest). The analytical technique used is descriptive analysis and N-Gain test. The results showed that student learning outcomes using the google classroom application increased before and after treatment, from 62.00% to 89.17%. Based on the N-Gain test, student learning outcomes are in the medium (47%) and high (53%). This shows that learning using the google classroom application in biology learning is quite effective in improving the learning outcomes of class XI science students at SMA Negeri 1 Talaga Raya